The Role of Local Government In Protection of Copyright Against Creative Industry Local Cultural Heritage In Sawahlunto City - Rifqi Dewi Lawra; Yulia Nizwana (Faculty of Law, Universitas Sebelas Maret, 2017)
Intellectual Property Rights (IPR) Â are closely related to the economic growth of a State. Appreciation and protection of intellectual works will create a conducive climate for the creativity and innovation of the people. IPR is a Right that is closely related to economic issues. IPR is identical with the commercialization of intellectual works. The commercialization of intellectual works in principle aims to generate economic benefits. Traditionally intellectual property is divided into two branches of